Cactus-Pear Juices - Sáenz, Carmen; Sepúlveda, Elena (Journal of the Professional Association for Cactus Development, 2001)
This paper presents a review of cactus-pear juice production. Its technological characteristics are considered, as well as the main difficulties in obtaining high-quality juice. Acidity, pigments, aroma, and other components play an important role in the cactus pear juice processing. Betalain and chlorophyll are present in purple and green cactus pear juices, and heat treatment of the juices affects their color, but the purple juice is more stable. Some lengthy thermal treatments cause an unattractive taste, like hay, and certain changes of aroma in the products. Some blends with other fruit juices, such as pineapple, could be an advantage in the technological process. The pineapple juice and the addition of citric acid decrease the pH of the blends, a positive action for their microbiological stability. Another cactus-pear juice alternative is juice from the orange cactus pear, but it has been studied less and requires, as with some aspects of the other types of juice, further investigation.